Phytochemical Molecules Binding with the Proteins of Mycolic Acid Synthesis Pathway of Mycobacterium tuberculosis - Rishabh Gaur; Praveen Kumar Anand (Journal of Molecular Docking, 2022)
Resistance against anti-tubercular drugs is a significant problem. This elucidates the need for novel drug targets. Altering and targeting the enzymes involved in cell wall synthesis led to fatal damage to the bacterial cell. Mycolic acids are critically responsible for the virulence of Mycobacterium Tuberculosis. This pathway represents an essential reservoir of novel targets for developing new TB drugs. The study aims to identify phytochemicals with the capacity to bind with enzymes of mycolic acid synthesis pathways. This study shows the interaction between phytochemicals and proteins responsible for mycolic acid synthesis is shown through bioinformatics & molecular docking tools. Docking showed binding affinity between protein molecules of the mycolic acid synthesis pathway and ligand molecules in the study. PKS13 (polyketide synthase) interacts with the ligand beta-amyrin acetate with a vina score of -7.1 Kcal/mol. At the same time, its binding energy with Piperine is -6.8 Kcal/mol. DprE1 (Decaprenylphosphoryl-bet-D-ribose-2-epimerase), the other protein docked with beta-amyrin acetate, showed a vina score of -9.7 Kcal/mol binding energy. Piperine with DprE1 exhibits interaction with a score of -8.3 Kcal/mol. Beta-amyrin acetate is docked with a score of -6.9 Kcal/mol against KasA (Beta-ketoacyl-acyl carrier protein synthase). On the other hand, Piperine with KasA gave a result of -7.0 Kcal/mol. Piperine and Beta-amyrin acetate binds to PKS13, DprE1 & KasA protein/enzymes responsible for mycolic acid biosynthesis.